2011
DOI: 10.1118/1.3544660
|View full text |Cite
|
Sign up to set email alerts
|

On the wall perturbation correction for a parallel‐plate NACP‐02 chamber in clinical electron beams

Abstract: The variation of the wall perturbation correction for the NACP-02 chamber in clinical electron beams strongly depends on the positioning of the chamber. Applying a shift deltaz = -0.058 cm toward the focus ensures that the primary electron spectrum within the chamber bears the largest resemblance to the fluence of a wall-less cavity. Hence, the influence of the chamber walls on the perturbation correction can be separated out and the residual variation of p(wall) with depth is minimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
4
8
0
Order By: Relevance
“…The model used in that work is based on the publication of Chin et al 22 who suggested that the mass thickness of the front wall of the NACP-02 chamber should be increased by about 50%. The result of Zink and Wulff 34 is similar to the corresponding value of 0.71 mm in Table II although the results of the present work also account for the effect of the air cavity on the electron fluence.…”
Section: B2 Comparison To Previous Calculationssupporting
confidence: 85%
See 2 more Smart Citations
“…The model used in that work is based on the publication of Chin et al 22 who suggested that the mass thickness of the front wall of the NACP-02 chamber should be increased by about 50%. The result of Zink and Wulff 34 is similar to the corresponding value of 0.71 mm in Table II although the results of the present work also account for the effect of the air cavity on the electron fluence.…”
Section: B2 Comparison To Previous Calculationssupporting
confidence: 85%
“…In what follows, we compare the calculated EPOM shifts obtained here with those obtained by other authors using Monte Carlo simulations of ion chamber response in electron beams. [32][33][34] Since the results of this work and all previous Monte Carlo calculated EPOM shifts used the EGSnrc code system, there is some correlation among the results discussed in this comparison.…”
Section: B2 Comparison To Previous Calculationsmentioning
confidence: 84%
See 1 more Smart Citation
“…A bigger challenge for parallel-plate ICs is defining the EPOM once the position of the outer wall is determined. A number of recent publications [13][14][15][16][17][18] have indicated that this is not necessarily congruent with the inside entrance window of the IC.…”
Section: Discussionmentioning
confidence: 98%
“…14, 15 The results will be applicable not only to the Markus chamber but also to the more recent designs of flat ionization chambers for electron beam dosimetry such as the Roos, Exradin A10, and the Advanced Markus chamber. Similarly to the experimental study performed by Johansson,8 we only consider wall-less cavities, i.e., the impact of the chamber wall always present in real ionization chambers will not be investigated.…”
Section: Introductionmentioning
confidence: 99%